A Corpus-based Analysis of the Media Representation of Feminism: International Evidence - Dr. Barly Jaworska; Dr. Vishanth Nigel (Al-Qanṭara, 2022)
Abstract The term "feminism" refers to a broad spectrum of political movements, ideologies, and social movements that have the shared objective of defining, establishing, and ultimately achieving the equality of the sexes in political, economic, personal, and social spheres. The central idea behind feminism is that it is necessary to fight for women's rights to equality and justice in all aspects of life, as well as to make it possible for women to have the same access to resources as men do when those resources are otherwise freely available. Since feminism covers such a wide range of topics, including the history of women's oppression as well as potential solutions to the problem of women's "anxiety of authorship" by creating a literary canon that is uniquely theirs, it is clear that feminism is an expansive field of study. Because there are many different psychosocial and cultural constructions of femininity, feminism is, in fact, a serious attempt to analyse, comprehend, and clarify these concepts. In spite of this, the purpose of this paper is to make an attempt to sketch out some of the fundamental premises and tenets of feminism, as well as to trace the theoretical origin of the movement by investigating a few works that were trend setters in the field of feminist literary theory.